The Impact of Environmental Performance and Profitability on Firm Value - Cicely Delfina Harahap; Ilyas Juliana; Febby Fitria Lindayani (Universitas Trisakti, 2018)
This research purposes to test and analyze the effect of Environmental Performance and Profitability on Firm Value. This study focuses on manufacturing companies in Bursan Efek Indonesia (BEI) in 2014-2016 which follows PROPER. This study used 22 companies with 66 observations. Environmental Performance (Independent Variables) proxies with PROPER, and Profitability is measured by ROA. Dependent variable used in this research is Company Value. This study uses a simple linear regression analysis. The result of the research, it is known that Environmental Performance has a positive effect on company value. While profitability does not affect on company value. The results of this study is expected to be a consideration of investors in making investment decisions and assess the performance of a company.